Cheap Talk and Strategic Rounding in LIBOR Submissions. (9th September 2019) - Hernando-Veciana, Ángel; Tröge, Michael
Abstract: Interbanking rates were, until recently, based on judgmental estimates of borrowing costs. We interpret this as a cheap-talk game that allowed banks to communicate nonverifiable information about their opportunity cost to potential counterparties. Under normal market conditions there is a welfare maximizing equilibrium where banks truthfully disclose their borrowing cost, but, in times of financial stress, only "coarse" equilibria survive. We take this prediction to the data and show that banks round more frequently if the risk of the bank increases. Rounding is also more frequent for the more liquid short-term rates and certain benchmark maturities. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.